Answer:
c. y= 2x - 1
Explanation:
Because the first one is x is -2 and y is -5 so you do 2 times x which is -2 which gives you -4 - 1 gives you y which is -5
Then the next one is x = -1 and y is -3 so you do 2 times -1 which is -2 then -2 minus 1 which is y -3
Then the next one is x = 0 and y = -1 so again you do 2 times 0 which is obviously 0 because anything that is multiplied by 0 is 0 so then 0 minus 1 is y= -1
the next one is x = 1 and y = 1 so you do 1 times -1 which is 2 times 1 which is 2 then minus 2 by 1 which is 1
and the last on is x=2 and y=3 so once again you do 2 times 2 which is 4 then minus 4 by 1 which is y=3
and if you still dont get it I will help you by showing you something just ask